PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI RIAU - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The research was conducted at Department of Industry and Trade of Riau Province. Based on the background of the research mentioned above, the authors can formulate the problem in this study is whether the Supervision significantly influence the Performance of Employees at the Office of Industry and Trade of Riau Province. The purpose of this study is to determine the effect of supervision on the performance of employees of the Office of Industry and Trade of Riau Province ..Data analysis in this research is done by using descriptive and quantitative method. Descriptive method of data analysis by decomposition of theories contained in the bibliography and associated with the data obtained from the results of research that will be collected, grouped and tabulated then taken conclusions. And the quantitative method with linear regression technique sedrhana .. The sample taken in this research is amounted to 69 people, Based on the above output obtained t-count value of 9.626 while for the value t_tabel obtained the value of t_hitung (9,626)> from t_tabel (1.99601), so it can be concluded that there is a significant effect of supervision on employee performance, obtained the value of R_square or coefficient of determination of 0.580, which has the meaning of the influence of supervisory variables against the kiner ja of 58.0% while the rest of 42.0% describe other independent variables that are not observed in this study.